A Signal-Based Data Fusion Approach in Non-DestructiveTesting of Composite Materials in the Aerospace Industry - Tom Avikasis Cohen; Anna Brook (e-Journal of Nondestructive Testing)
Non-Destructive Testing (NDT) plays a crucial role in